Združevanje družin priseljencev v izbranih državah članicah Evropske unije - Pirc, Janez (Razprave in gradivo - Inštitut za narodnostna vprašanja (1990), 2009)
Family reunification of immigrants in selected EU member states. This article provides an overview and comparison of the selected European Union Member States governing the right to family reunification. The basis for this comparative analysis presents Directive (2003/86/EC), since all the countries were obliged to incorporate its contents into their national legislation. In this context, I assessed how the selected countries deviate from the Directive according to the specific criteria and how they differ. The article focuses on the following questions: which family members are covered by this right; what conditions must be completed by the sponsor and family members for family reunification; the length of the procedure of decision on the request for family reunification and the period the sponsor must spend in the Member State before having his/her family members join him/her; the rights belonging to the family members with the implementation of family reunification. The article presents the historical and current context of legal migration and family reunification in the European Union. In this context, it highlights the key international documents, which led to the creation of common migration policy of the European Union in this area as wellas critically analyzes the content of the Directive.
Keywords: European Union; Evropska unija; imigranti; human migration; migracije; mednarodne migracije; family; družina; človekove pravice; human rights; migracijska politika; zakonodaja; direktive